(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study investigated the impact of ethical school administration on secondary education goals attainment in Yakurr Local Government Area of Cross River State, Nigeria. One research question and hypothesis was formulated to guide the study. The study adopted correlation design. The population of this study comprises all the 17 public secondary school and 346 teachers in Yakurr Local Government Area, Cross River State. Census approach was adopted in the study. An instrument titled “Ethical School Administration and Secondary Education Goals Attainment. Questionnaire (ESASEGAQ)” was used for data collection. The questionnaire was face and content validated by three research experts from the department of Educational Management, and from Measurement and Evaluation, faculty of Educational Foundation Studies, University of Calabar. The reliability was determined through Cronbach alpha technique and the index ranges between .88 - .90. The descriptive statistics output of the Simple Linear Regression Analysis was used to answer the research question, while the ANOVA and relative coefficient output of Simple Linear Regression Analysis was used to test the hypotheses at 0.05 level of significance. The result of the analysis revealed that ethical school administration significantly predict secondary education goals attainment (R=.638). Based on the findings of the study, it was concluded that ethical school administration statistically predict secondary education goals attainment in Yakurr Local Government Area, Cross River State. This underscores the importance of integrity, fairness, transparency, and accountability in school leadership as critical determinants of educational outcomes. It was recommended that Cross River State Ministry of Education in collaboration with the management of secondary schools should organize regular training and capacity-building workshops on ethical leadership for school administrators to strengthen their commitment to ethical practices in other to enhance the attainment of secondary education goals in public schools.